Economic Analysis of Traditional and Sri Method of Paddy Cultivation - Shende, N. V.; Shende, P. V.; Thorat, R. S. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The conventional paddy growing tracts are in worst crisis due to social, biological and technical setbacks. Well acclaimed rice bowls in several part of the nation is facing a decline in area, production and productivity. In India, there is a growing demand for rice due to ever escalating population. Rice is consumed both in urban and rural area and its consumption is growing due to high-income elasticity of demand. To meet the growing demand, a rapid income in paddy production is needed. But there is little scope to increase the area; hence increase in production and productivity with an improvement in efficiency of production to act as a technological breakthrough to meet the growing demand.